2020
DOI: 10.22207/jpam.14.spl1.37
|View full text |Cite
|
Sign up to set email alerts
|

In silico Molecular Docking Analysis Targeting SARS-CoV-2 Spike Protein and Selected Herbal Constituents

Abstract: In modern drug discovery, molecular docking analysis is routinely used to understand and predict the interaction between a drug molecule and a target protein from a microbe. Drugs identified in this way may inhibit the entry and replication of pathogens in host cells. The SARS-CoV-2 associated coronavirus disease, COVID-19, has become the most contagious and deadly pandemic disease in the world today. In abeyance of any specific vaccine or therapeutic against SARS-CoV-2, the burgeoning situation urges a need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 42 publications
(30 reference statements)
1
26
0
2
Order By: Relevance
“…It has been described that a high intake of turmeric ( Curcuma ) in the diet has beneficial effects against inflammation, apoptosis, and RNA replication. Suppression of pulmonary edema and fibrosis-associated pathways in COVID-19 infection has also been reported [82] . Curcumin derivatives inhibit human A influenza virus in vitro , and docking studies propose curcumin as a potential inhibitor of spike protein binding to ACE-2 [80] , as well as of M pro [81] .…”
Section: Considerations From a Medical Perspectivementioning
confidence: 86%
“…It has been described that a high intake of turmeric ( Curcuma ) in the diet has beneficial effects against inflammation, apoptosis, and RNA replication. Suppression of pulmonary edema and fibrosis-associated pathways in COVID-19 infection has also been reported [82] . Curcumin derivatives inhibit human A influenza virus in vitro , and docking studies propose curcumin as a potential inhibitor of spike protein binding to ACE-2 [80] , as well as of M pro [81] .…”
Section: Considerations From a Medical Perspectivementioning
confidence: 86%
“…The structures of the hits identified from these computational studies could be optimized as part of the drug discovery process (Ojha et al, 2020 ). In addition to synthetic pharmacological compounds, herbal constituents can be screened in the same manner and this method has been described in many papers (Bhowmik et al, 2020 ; Chikhale et al, 2020 ; Ghosh et al, 2020 ; Gupta et al, 2020 ; Jena et al, 2020 ; Krupanidhi et al, 2020 ; Muhseen et al, 2020 ; Sinha et al, 2020 ; Subbaiyan et al, 2020 ). A number of studies that can be found on the World Health Organization's International Clinical Trials Registry Platform also involve plant-based compounds, particularly flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to be a precursor of hypericin [70], and possibly also the precursor of fagopyrin. Emodin isolated from Tartary buckwheat grain [71] has been shown to bind well to all three active sites of the RNA binding domain of the nucleocapsid phosphoprotein of Sars-CoV-2 [70,72,73]. However, the biosynthesis pathways of emodin in Tartary buckwheat remain unclear to date [74].…”
Section: Fagopyrin and Emodinmentioning
confidence: 99%